ANALISIS BIBLIOMETRIK DALAM PENELITIAN PERANGKAT LUNAK MIKE 21 DALAM INDUSTRI KONSTRUKSI - Rahayu, Sri; Sabitri, Zenita; Ghinaya, Zahra; Wiharja, Hery (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2023)
Mike 21's technological developments contribute to the progress of infrastructure and the living environment, providing efficient and sustainable solutions. This study aims to measure the development of the use of Mike 21 software in the field of civil engineering in Indonesia. The study used bibliometric analysis methods with the help of VOSViewer software. Further analysis of related terms resulted in 237 terms, 204 of which were selected for mapping visualization that considered relevance and correlation with Mike 21’s research. The mappings prove that the development of research in the field of civil engineering has direct correlations with the use of Mike 21 software. The results of the research through a literature review using the Publish or Perish reference management application, identified 991 Google Scholar indexed journal articles relevant to the theme 'Mike 21 in civil engineering publication development in Indonesia'. The study matrix found that the entire article had a total of 22,227, with an average of 22.32 citations per article and an annual average of 2.469.67 and the highest number of publications published in 2020. Research that uses Mike 21 in the field of Civil Engineering is on the rise, making a positive contribution to future infrastructure and living environmental progress